1998
DOI: 10.1093/oxfordjournals.jbchem.a022223
|View full text |Cite
|
Sign up to set email alerts
|

A New Low Density Lipoprotein Receptor Related Protein, LRP5, Is Expressed in Hepatocytes and Adrenal Cortex, and Recognizes Apolipoprotein E

Abstract: The isolation and characterization of rabbit and human cDNAs revealed a new low density lipoprotein receptor (LDLR)-related protein (LRP) designated as LRP5. Human LRP5 cDNA encodes a 1, 616-amino acid type I membrane-like protein with three ligand binding repeats in its extracellular region. LDLR-deficient cells transduced by recombinant adenovirus containing human LRP5 exhibited increased binding of apolipoprotein E (apoE)-enriched beta-migrating very low density lipoprotein. Northern blotting and in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 9 publications
0
87
0
3
Order By: Relevance
“…In recent years it has become clear that the highly homologous LRP5 LRP6 (Brown et al, 1998) proteins are crucial for reception of the Wnt signal transduction pathway (Pinson et al, 2000;Tamai et al, 2000;Wehrli et al, 2000). Although we lack conclusive evidence regarding the interaction between LRP5/6 and APOE at the cellular and molecular levels, it has been proposed that LRP5/6 may recognize and be involved in APOE catabolism (Kim et al, 1998;Magoori et al, 2003). Moreover, recent experiments suggest that apolipophorins, the ortholog for APOE proteins in Drosophila, copurify and act as vehicles for the movement of lipid-linked morphogens including the Wnt ortholog Wingless (Panakova et al, 2005).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 85%
“…In recent years it has become clear that the highly homologous LRP5 LRP6 (Brown et al, 1998) proteins are crucial for reception of the Wnt signal transduction pathway (Pinson et al, 2000;Tamai et al, 2000;Wehrli et al, 2000). Although we lack conclusive evidence regarding the interaction between LRP5/6 and APOE at the cellular and molecular levels, it has been proposed that LRP5/6 may recognize and be involved in APOE catabolism (Kim et al, 1998;Magoori et al, 2003). Moreover, recent experiments suggest that apolipophorins, the ortholog for APOE proteins in Drosophila, copurify and act as vehicles for the movement of lipid-linked morphogens including the Wnt ortholog Wingless (Panakova et al, 2005).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 85%
“…Whereas Lrp6 mutants have a reduced number of osteoblasts, Lrp5 primarily regulates the mineralization process. With regard to metabolism, both receptors retain the capacity to bind lipoproteins (71)(72)(73), and, much like LRP5, mutations in LRP6 are associated with metabolic dysfunction in humans (33,74). One potential explanation for the functional difference in osteoblasts may relate to the expression pattern of the coreceptors during osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been proposed that LRP5/6 may recognize and be involved in APOE catabolism of plasma lipoproteins (65,66). Likewise, it was shown that apolipophorins, the ortholog for APOE proteins in Drosophila, copurify and act as vehicles for the movement of lipid-linked morphogens including the Wnt ortholog Wingless (67).…”
Section: Discussionmentioning
confidence: 99%